2001
DOI: 10.1093/toxsci/63.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Effects of Respirable Quartz Collected in Workplaces versus Standard DQ12 Quartz: Particle Surface Correlates

Abstract: In 1997, the IARC (International Agency for Research on Cancer) reevaluated its quartz classification from a class 2 carcinogen, to that of a class 1, stating sufficient evidence for carcinogenicity in both humans and experimental animals. However, tumor development did not occur across all occupational settings. It is probable that this is due to the considerable differences in toxicity between workplace quartz in comparison to quartz used in experimental studies. We therefore hypothesized that workplace quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 34 publications
5
89
0
1
Order By: Relevance
“…As with acute exposures , the repeated exposure strategy was validated by repeatedly aerosolizing DQ12 crystalline quartz as a positive inflammatory control. Results showed that DQ12 introduced a statistically significant increase in the secretion of the (pro)-inflammatory proteins IL-1b and TNF-a after both repeated exposure scenarios and consequently a biological relevant increase in IL-8, which clearly indicates that (pro-)inflammatory response can be triggered in the system by classical materials known for their inflammatory properties, such as DQ12 (Clouter et al, 2001). These findings further confirm the sensitivity of the in vitro system.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As with acute exposures , the repeated exposure strategy was validated by repeatedly aerosolizing DQ12 crystalline quartz as a positive inflammatory control. Results showed that DQ12 introduced a statistically significant increase in the secretion of the (pro)-inflammatory proteins IL-1b and TNF-a after both repeated exposure scenarios and consequently a biological relevant increase in IL-8, which clearly indicates that (pro-)inflammatory response can be triggered in the system by classical materials known for their inflammatory properties, such as DQ12 (Clouter et al, 2001). These findings further confirm the sensitivity of the in vitro system.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, crystalline Dörentruper Quartz (DQ12; 5 mm; Robock, 1973) at a concentration of 0.1 mg/ml ) was used as a positive (pro-)inflammatory ''particle control'', since it is known to induce severe pulmonary inflammation (Clouter et al, 2001;Monteiller et al, 2007).…”
Section: Mwcnts and Positive Controls Samplesmentioning
confidence: 99%
“…45 Indeed, DQ12-exposed animals have been observed to express severe inflammatory effects following either 14d or 90d of exposure, respectively. 46,47 Therefore, the ability of DQ12 to trigger (pro-)inflammatory reactions at both the gene and protein level highlights the effectiveness of the employed in vitro chronic strategy. Notably, the highest cytokine expression in DQ12-exposed cells was observed at w3 followed by a decrease over the last week, indicating a possible cell threshold or recovery from the repetitive challenge with DQ12.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been suggested that the presence of highly reactive radicals on the surfaces of fractured silica that may be present in certain workplaces make the fractured silica highly cytotoxic (Castranova et al, 1996;Clouter et al, 2001). Dobias et al (2006) suggested that quartz dust is genotoxic and is an important contributor to the genotoxicity of complex mixtures of fibrogenic respirable airborne particles in ambient air in certain workplaces.…”
Section: Introductionmentioning
confidence: 99%